The Nexus of Government Spending, Price, Output, and Money in the ECOWAS Sub-Region: Evidence from Panel ARDL and Causality Approach - Dada, Matthew Abiodun; Posu, Sunday Mauton A.; Okungbowa, Osaretin Godspower; Abalaba, Bamidele P. (Economics and Business, 2021)
The question of how macroeconomic variables dynamically interact is very crucial in any broad-based economic integration aiming at expanding economic growth and living standard in any human society. This study examined the nexus of government spending, price, output, and money in the ECOWAS sub-region using panel ARDL and causality approach. Data covering the period (1981–2019) were collected mainly from the latest version of the World Development Indicators. The result showed a positive relationship between government spending with GDP, import, exchange rate, unemployment rate, and population growth rate but a negative relationship between government spending with inflation, money supply, export, and interest rate. The result further showed short-run unidirectional causality running from government spending to inflation, money supply to inflation as well as money supply to GDP. Short-run bi-directional causality existed between GDP and inflation but none between government spending and GDP nor between government spending and money supply. The result of long-run Granger causality test showed bi-directional causality between government spending with inflation, government spending, and money supply; GDP and inflation; and GDP and money supply. Unidirectional causality ran from GDP to government spending; and money supply to inflation. The overall implication of this study established that an increase in government spending lowered inflation and raised the living standard of people in the ECOWAS sub-region in the long run. The study therefore concluded that any rise in import, unemployment rate, exchange rate, and population growth rate would raise government spending growth rate in the short run; and an increase in government spending would shrink inflation and boost economic growth and living standard in the long run.